Yahoo Web Search

  1. r = -3sec(θ) Change secant to cosine form by definition of secant: r = -3/cos(θ) Multiply both sides by cos(θ): rcos(θ...

    4 Answers · Science & Mathematics · 21/05/2008

  2. r ^3 + 0.008 = r ^3 - (- 2 / 10)^3 <=> r ^3 + 0.008 = ( r + 0.2) * (r² - 0.2 * r + 0.04)

    3 Answers · Science & Mathematics · 29/03/2009

  3. r = sin(theta) + 1 r = sin(t) + 1 recall that y = r *sin(t) r = y/ r + 1 r² = y + r x² + y² = y + √(x² + y²)

    2 Answers · Science & Mathematics · 16/05/2011

  4. 2/( r ( r ^2 -1))=A/( r +1) + B/ r + C/( r -1) 2/ r /( r -1)/( r +1)=..... multiply...=2 A=3 B=2 C=0 is a solution for R =3 But so is A=0 B=2 C=1...

    2 Answers · Science & Mathematics · 27/06/2010

  5. Hi cajntaz, The DVD+ R and DVD- R are competing .... However, because the DVD- R format has been in use since 1997, it ...

    4 Answers · Consumer Electronics · 25/01/2008

  6. By factoring, we have: r /( r + 3) + 4/( r - 2) = 20/(( r - 2)( r + 3)) Multiply both sides by... + br + c, let: a = 1 b = 2 c = -18 Next, by quadratic formula: r = (-b ± √(b² - 4ac))/2a ==> (-2 ± √((2)² - 4*1*-18))/2 ==> (-2...

    4 Answers · Education & Reference · 02/04/2011

  7. I=E/( R + r ) multiply both sides of the equations by ( R + r ): I... subtract r from both sides of the equation: R =(E/I) - r *Note: lol wise guy..you were still right in your first...

    2 Answers · Science & Mathematics · 20/02/2008

  8. 10.5 = R *12^2 / (1.49 + R )^2 Simplify: 10.5= R *144/(1.49+ R )^2 Expand: 10.5= R *144/1.49^2+ R ^2 Simplify again: 10.5= R *144/2.2201+ R ^2 10.5= R ...

    2 Answers · Education & Reference · 30/09/2010

  9. Add 102.7 to both sides (1/(1+ r )) * (29.4/ r ) = 102.7 multiply (1/(1+ r )) * (29.4/ r ) 29.4/[(1+ r )( r )] = 102.7 .... 0 = 102.7r + 102.7r^2 - 29.4 Use the quadratic formula to find r . http://www.purplemath.com/modules/quadform.htm - this site shows the formula...

    1 Answers · Science & Mathematics · 18/10/2009

  10. [( r + 2)^3 - 8] = ( r +2 - 2)(( r +2)^2 + 2( r +2) + 4) = [ r ( r ^2 + 4r + 4 + 2r + 4 + 4)] = r ( r ^2 + 6r + 12) so: 1) lim g ( as r approaches 0) = lim r ( r ^2 + 6r + 12) / r = lim ( r ^2 + 6r + 12...

    1 Answers · Science & Mathematics · 29/03/2009

  1. Try asking your question on Yahoo Answers